Description of Assessment: Assessment for Learning and Assessment as Learning on Teacher Learning Assessment - Hidayat, Rahmad; Sujadi, Imam; Siswanto; Usodo, Budi (Journal of Education Reseach and Evaluation, 2023)
Assessment becomes a self-developing learning instruction and requires a broader focus on feedback interventions, especially learners' responses to feedback and the learning environment in which feedback works. Study of the ability of teachers to reflect on the application of assessment in the learning process in the classroom. The purpose of this study is to analyze Assessment for Learning (AfL) and Assessment as Learning (AaL) in the learning process in the classroom. The research method used is a qualitative research method using an in-depth, focused interview. Data collection techniques in the form of reflective are analyzed using reduction analysis, presentation, and drawing conclusions from the data. The results of the interviews show that assessment is often used as a measure of learning success alone, without regard to the application of constructive feedback to help students improve their achievement competencies in mathematics learning. Assessment is still focused on giving grades or rankings that can result in competition between students, so they have not focused on improving the learning process. It gives stakeholders a clear and unified picture of how educational assessments relate to learning and can help educators assist and design assessment practices. The construct of Assessment for Learning (AfL) and Assessment as Learning (AaL) must be looked at consistently with each other to build an assessment culture that maximizes student learning.